Larval morphology and natural history in two Minervarya species from Andaman Islands, with comments on a new phytotelmonous larval morphotype for the genus - Gopika, C.; Garg, Sonali; Sivaperuman, Chandrakasan; Gokulakrishnan, G.; Biju, S. D. (Zootaxa, 2023)
We studied the larval morphology and natural history of two species of Minervarya from the Andaman Islands of India. A recent assignment of Charles Darwin’s frog to the genus Minervarya opened up new questions on the systematic affinities and natural history of its enigmatic tadpoles. Originally described as Rana charlesdarwini Das, 1998, and long considered as Ingerana charlesdarwini, the tadpoles of this species were poorly understood and incomparable to those of other presumed close relatives based on an original brief description of its phytotelmonous tadpoles. Here we present a detailed redescription of the larval morphology of M. charlesdarwini based on genetically confirmed tadpoles. At the same time, we compared the external morphology of M. charlesdarwini tadpoles to that of its closest phylogenetic and sympatric congener, M. andamanensis, consequently reporting the first-ever larval description for M. andamanensis. For the first time also for minervaryan frogs, we record that M. charlesdarwini lays eggs on the inner walls of tree holes, and the tadpoles possess morphological adaptations for a phytotelmonous life. Their unique features, such as tail-to-body ratio >2.2, reduced labial tooth rows (LTRF 1/1), acutely pointed serrations in the jaw sheath, and the medial portion of the upper sheath broadly arched and that of the lower sheath U-shaped, justify adding a new larval morphotype to the genus Minervarya. In contrast, M. andamanensis breeds and undergoes development in ground water puddles and ponds, a common trait for other known minervaryan species. Furthermore, our study generates new knowledge on the amplexus, oviposition site, and early embryonic development in these species. The deeper understanding of the biology and habitat requirements contributes additional traits for future systematic and evolutionary studies, and helps guide conservation assessments for these two species endemic to a handful of islands in the Andaman Archipelago.